Development of CARRA/PReS-endorsed consensus Core and Expanded Datasets in childhood-onset systemic lupus erythematosus for international registry-based research - Sadun, Rebecca E.; Cooper, Jennifer C.; Belot, Alexandre; Avcin, Tadej; Aggarwal, Amita; Ainsworth, Jenny; Akinsete, Alisha; Ardoin, Stacy P.; Beresford, Michael W.; Bortey, Lynette; Brunner, Hermine I.; Chang, Joyce C.; et al. (Elsevier, 2025)
Objectives: Childhood-onset systemic lupus erythematosus (cSLE), representing 15%–20% of individuals with SLE, has been difficult to study globally due to differences between registries. This initiative, supported by Childhood Arthritis Rheumatology Research Alliance (CARRA) and Paediatric Rheumatology European Society (PReS), aims to create Core and Expanded cSLE Datasets to standardise and enhance research worldwide. Methods: 21 international cSLE experts and 4 patients participated in a Delphi process (questionnaires, 2 topic-specific focus groups and 3 virtual consensus meetings) to create 2 standardised cSLE datasets. The Core cSLE Dataset was designed to include data essential to meaningful clinical research across many settings. The Expanded cSLE Dataset was designed for centres able to consistently collect data to address broader research questions. Final data items for the Core and Expanded datasets were determined by consensus defined as >80% agreement) using an adapted nominal group technique and voting. Results: The resulting Core cSLE Dataset contains 46 items, including demographics, clinical features, laboratory results, medications and significant adverse events. The Expanded cSLE Dataset adds 26 additional items and includes patient-reported outcomes. Consensus was also achieved regarding the frequency and time points for data collection: baseline, quarterly follow-up visits, annually and flare visits. Conclusion: Standardised Core and Expanded cSLE Datasets for registry-based international cSLE research were defined through the consensus of global experts and patient/caregiver representatives, endorsed by CARRA and PReS. These datasets incorporate disease-specific and patient-specific features, optimised for diverse settings to facilitate international collaborative research for children and adolescents with SLE worldwide.
Keywords: Child; Health Care; Lupus Erythematosus; Lupus Nephritis; Outcome Assessment; Patient Reported Outcome Measures; Systemic